Trainer Competence as a Key Driver of Member Performance in Digital Live-Streaming Work - Riska Nuraini; Mariana Puspa Dewi (Al-Qalam Institue, 2026)
This study aims to analyze the effects of training and trainer competence on member performance. A quantitative approach using a survey method was employed. The population consisted of 57 members, all of whom were selected as the sample using a saturated sampling technique. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression with IBM SPSS Statistics version 27. The results indicate that training has no significant effect on member performance, as shown by a t-value of 0.766, lower than the t-table value of 2.005, with a significance level of 0.448 (>0.05). In contrast, trainer competence has a positive and significant effect, with a t-value of 3.889 and a significance level of 0.001 (<0.05). Simultaneously, training and trainer competence significantly affect member performance, with an F-value of 27.323 and significance <0.001. Trainer competence has the stronger influence. The Adjusted R-square of 0.534 indicates that 53.4% of the variance in member performance is explained by the two variables. These findings imply that improving trainer competence should be prioritized to enhance member performance.